Expanding fields of architectural discourse and practice : curated works from the P.E.A.R. journal - Butcher, Matthew; O'Shea, Megan (UCL Press, 2020)
Expanding Fields of Architectural Discourse and Practice presents a selection of essays, architectural experiments, and works that explore the diversity within the fields of contemporary architectural practice and discourse. The book pays particular attention to the question of how and why architecture can and should manifest a critical and reflective capacity outside of its primary function; it also closely examines the ways the discipline currently resonates with contemporary art practice. It does so by reflecting on the first ten years of the architectural journal P.E.A.R ... The book features contributions by architectural practitioners, design researchers, artists, architectural theorists, historians, journalists, curators, and even a paleobiologist, all of whom contributed to the journal. Here, they provide a unique presentation of architectural discourse and practice that seeks to test new ground while forming distinct relationships to recent, and more longstanding, historical legacies.